Open Banking and automated transaction analysis in the digitalization of business banking: Design, opportunities, and challenges of a digital credit process - Ruven Henkler; Constantin Schubart (IU Internationale Hochschule, 2025)
In the digital age, banks must urgently transform their traditional lending processes. This necessity is intensified by the growing competition from digital providers and customers' increasing expectations for efficiency and speed in financial services. Particularly in the business banking sector, traditional credit processes are often characterized by lengthy processing times and inefficient manual procedures, significantly limiting banks' ability to respond promptly to customer inquiries. This paper examines the role of open banking and automated transaction analysis as key factors in the digital transformation of lending. By integrating real-time data and advanced analytics, banks can make more informed credit decisions and greatly enhance customer satisfaction. At the same time, the risks and challenges associated with implementing these technologies, particularly regarding data protection, regulatory requirements, and technical infrastructure, are critically assessed. This investigation's findings provide valuable insights for financial institutions striving to remain competitive in a rapidly changing digital environment and underscore the need to rethink traditional lending processes fundamentally.
Keywords: G20; G21; L86; M15; O32; O33; 650; Open Banking; PSD2; FinTech; Business Banking; Digital Lending; Business Processes; Digital Transformation